2012
DOI: 10.1002/jbm.b.32660
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of intrabony defects with beta‐tricalciumphosphate alone and in combination with platelet‐rich plasma

Abstract: Background:The therapeutic efficacy of platelet‐rich plasma (PRP) still remains controversial. This study aimed to compare the efficacy of a beta‐tricalcium phosphate (β‐TCP) and PRP/β‐TCP combination both clinically and radiographically.Methods:Fourteen chronic periodontitis patients with at least two similar three‐walled defects were included in the study. Each patient was randomly treated with both β‐TCP (n = 14) and PRP/β‐TCP (n = 14) in the same session. Baseline and 6‐month evaluations of plaque index (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 36 publications
2
34
1
2
Order By: Relevance
“…The volumetric results of the present study are in line with previously reported studies using b-TCP for GBR [16,18,34,35]. Brkovic et al [14] reported that placement of b-TCP along with collagen membrane in extraction sockets resulted in good-quality healed bone which was capable of supporting implants.…”
Section: Discussionsupporting
confidence: 94%
“…The volumetric results of the present study are in line with previously reported studies using b-TCP for GBR [16,18,34,35]. Brkovic et al [14] reported that placement of b-TCP along with collagen membrane in extraction sockets resulted in good-quality healed bone which was capable of supporting implants.…”
Section: Discussionsupporting
confidence: 94%
“…These results are concomitant with earlier studies. [1920] This could be because of the regular and frequent recall visits in which the patients underwent regular supragingival scaling, which further minimized plaque accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…It is commercially available as blocks or granules. There are several papers combining TCP to GF, with positive and negative results 40,44 . Afifi et al 45 have demonstrated that TCP alone has a non-negligible tax of complications in cranioplasties, especially when inserted in previously irradiated areas, or for those in contact with paranasal sinuses.…”
Section: Discussionmentioning
confidence: 99%